2007
DOI: 10.1186/1746-1340-15-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical spinal decompression therapy: does the scientific literature support efficacy claims made in the advertising media?

Abstract: BackgroundTraction therapy has been utilized in the treatment of low back pain for decades. The most recent incarnation of traction therapy is non-surgical spinal decompression therapy which can cost over $100,000. This form of therapy has been heavily marketed to manual therapy professions and subsequently to the consumer. The purpose of this paper is to initiate a debate pertaining to the relationship between marketing claims and the scientific literature on non-surgical spinal decompression.DiscussionOnly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Recently, its advertised www.journalchiromed.com effectiveness has been called into question. 1 To date, we found 3 current spinal decompression tables published in PubMed journals: VAX-D therapy (VAX-D Medical Technologies, Oldsmar, FL), [2][3][4][5][6][7][8] DRS System (Cluster Technology Corporation, defunct), 9 and IDD Therapy (North American Medical Corp., Marietta, GA). 10 The common perception is that spinal decompression therapy is effective at treating disk pathologies, according to advertisements in chiropractic trade publications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, its advertised www.journalchiromed.com effectiveness has been called into question. 1 To date, we found 3 current spinal decompression tables published in PubMed journals: VAX-D therapy (VAX-D Medical Technologies, Oldsmar, FL), [2][3][4][5][6][7][8] DRS System (Cluster Technology Corporation, defunct), 9 and IDD Therapy (North American Medical Corp., Marietta, GA). 10 The common perception is that spinal decompression therapy is effective at treating disk pathologies, according to advertisements in chiropractic trade publications.…”
Section: Introductionmentioning
confidence: 99%
“…Over the year, many studies have demonstrated its positive effects on cervical and lumbar spine-related pain [4] [5] [6]. However, some review studies [7] [8] [9] pointed out that further research is needed, since there is not enough conclusive evidence to fully support the contribution of the therapy. Therefore, it is important to conduct a qualitative study on the mechanics of the therapy.…”
Section: Cervical Traction Therapymentioning
confidence: 99%
“…A herniated IVD is under constant elevated intradiscal pressure [2,28,29] and if intradiscal pressure can reduce, then perhaps a healing/regenerative response can occur. Non-surgical technology can therapeutically reduce intradiscal pressure and may allow for degenerative spinal conditions to regenerate, and more specifically, rehydrate.…”
Section: Non-surgical Spinal Decompressionmentioning
confidence: 99%